2012
DOI: 10.1016/j.biocon.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

What drives human–carnivore conflict in the North West Province of South Africa?

Abstract: Alleviating human-carnivore conflict is central to large carnivore conservation and is often of economic importance where people co-exist with carnivores. However, effective conflict mitigation requires knowledge of underlying human and environmental drivers that is largely absent in South Africa. From 2006 to 2008, we interviewed land owners in the North West Province of South Africa to quantify; 1) human-carnivore conflict characteristics and; 2) determinants of perceived predation levels and retaliatory per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 28 publications
(57 reference statements)
4
116
0
Order By: Relevance
“…Similar results have been suggested for other studies in South Africa where distance to protected areas influences predation rates by large carnivores (Thorn et al 2012). Risk of predation was greatest at low altitudes (Game: 775-790 m Livestock: 670-780 m) and at high altitudes (Game: 900-920 m Livestock: 1540-1760 m) reflecting differences in surface ruggedness between land use types and livestock husbandry practices.…”
Section: Spatial Patterns Of Leopard Predationsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results have been suggested for other studies in South Africa where distance to protected areas influences predation rates by large carnivores (Thorn et al 2012). Risk of predation was greatest at low altitudes (Game: 775-790 m Livestock: 670-780 m) and at high altitudes (Game: 900-920 m Livestock: 1540-1760 m) reflecting differences in surface ruggedness between land use types and livestock husbandry practices.…”
Section: Spatial Patterns Of Leopard Predationsupporting
confidence: 91%
“…Levels of loss were similar to those reported in the NorthWest Province of South Africa, (Thorn et al 2012) and 2.2 % in Botswana (Schiess-Meier et al 2007), but this finding contrasts with other studies on large carnivores where natural causes of mortality predominate (Dar et al 2009;Hemson et al 2009). Leopards accounted for 60 % of livestock attacks in the Blouberg, much higher than other regions in South Africa such as the Waterberg (Thorn et al 2012) although in line with similar rates reported in Botswana (Schiess-Meier et al 2007). Leopards in the Blouberg predate on young calves and donkey foals similarly, 64 % of reported depredation by leopards in the neighbouring Soutpansberg Mountains occurred on young calves (Chase-Grey 2011).…”
Section: Impacts Of Game and Livestock Loss By Leopardssupporting
confidence: 72%
See 2 more Smart Citations
“…Persecution is typically carried out to minimize real or perceived damage (Inskip and Zimmermann, 2009, but see Marchini and MacDonald, 2012 for an exception). It is often, but not always, directed towards large carnivores (e.g., Reynolds and Tapper, 1996;Thorn, Green, Dalerum, Bateman and Scott, 2012). Two characteristics of persecution make it potentially destabilizing on game numbers.…”
Section: Motivational Drivers Behind Huntingmentioning
confidence: 99%